PENGARUH PROMOSI TERHADAP TINGKAT HUNIAN KAMAR PADA MESRA BUSINESS DAN RESORT HOTEL DI SAMARINDA - Andini Indria Sari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
Promotion activities carried out by a company are a combination of the variables contained in the promotion mix, these variables include advertising, direct sales, sales promotion, publicity and word of mouth. The purpose of this research is to test and analyze the effect of the promotion of room occupancy rates at the Mesra Business and Resort Hotel in Samarinda. Promotion (X) is an independent variable while Occupancy Rate (Y) is a dependent variable. Primary data were obtained by conducting interviews with 70 respondents using a questionnaire. Secondary data obtained by conducting field observation. Data were analyzed using a simple linear regression method with the help of SPSS statistical software version 23. The result showed that the promotion variables consisting of advertising, direct sales, sales promotion, publicity and word of mouth simultaneously had a significant effect on room occupancy rates. Mesra Business and Resort Hotel should increase their promotional activities through the internet, be it the official website or existing social media. Wich can be accessed anytime, anywhere.